2005
DOI: 10.1093/ndt/gfi236
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification and cardiovascular function in chronic kidney disease

Abstract: This study has successfully utilized a novel technique for the quantification of calcification. We have demonstrated vascular calcification and associated cardiovascular dysfunction in CKD 4, PD and HD with significant differences between the groups. Thirty percent of individuals show no calcification, even those established on renal replacement therapy for a prolonged period of time. Further work is required to identify factors which promote progression of arterial calcification in those who are susceptible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 20 publications
7
128
3
3
Order By: Relevance
“…4 Previous reports have demonstrated that marked vascular calcification and stiffness predisposed hemodialysis patients to LVH and cardiac diastolic dysfunction. 21 We investigated the impact of fetuin-A and OPG serum levels, which are representative of potent vascular calcification regulators, on vascular stiffness and ventricular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Previous reports have demonstrated that marked vascular calcification and stiffness predisposed hemodialysis patients to LVH and cardiac diastolic dysfunction. 21 We investigated the impact of fetuin-A and OPG serum levels, which are representative of potent vascular calcification regulators, on vascular stiffness and ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Vascular calcification, which results in increased vascular stiffness, is a common pathological feature of hemodialysis patients 1,3 and is accompanied by left ventricular hypertrophy (LVH) and diastolic dysfunction. 4,5 Vascular calcification is an active process controlled by a balance of serum calcification inhibitors and enhancers. Fetuin-A (a2-Heremans Schmid glycoprotein) is a 62-kDa liver-derived glycoprotein and potent circulatory inhibitor of vascular calcification, which is downregulated by inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Multislice computerized tomography was used to quantify vascular calcification (VC) in a standardized section of the superficial femoral artery as described previously (18). Carotid-femoral pulse wave velocity (PWV) was measured using a SphygmoCor (AtCor Medical Pty, Ltd., Australia).…”
Section: Assessment Of Vascular Calcification and Pulse Wave Velocitymentioning
confidence: 99%
“…Several studies have shown that vascular calcification is present in 30-70% of adult patients with CKD [18] , and even in approximately 15% of uremic pediatric patients [19] . Arterial aging associated with ESRD is characterized by intimal as well as medial calcification.…”
Section: Interactions Between Inflammation and Vascular Calcificationmentioning
confidence: 99%